Peran Modal Usaha Terhadap Minat Berwirausaha Batik Tulis Tanjung Bumi - Anindita Trinura Novitasari (Departement of Mathematics Education, 2023)
MSMEs as part of the economic sector have driven many wheels of the community's economy through equitable distribution of people's income, provision of employment for productive working age, and specialization of products produced by each region. As a sector that has driven the wheels of the economy a lot and contributed positively to the national economy, the government is promoting MSMEs which continue to be developed in the community. However, in its development, MSMEs are not as easy as expected. There are many challenges and obstacles in the development of MSMEs. In terms of capital and financing, the skills of the workforce and business actors, information and technology, and the need for business actors to always innovate and this is not easy because the business actors of Tanjung Bumi batik are located in remote areas with minimal information, the education level of business actors is low. low ambition, the nature of the business which is family and hereditary and the people who are still not familiar with technology. The element of capital is the main and crucial element in running a business. We know that the element of capital cannot be denied its contribution to the running of the business. If the capital is strong, the business will easily develop. Financing will be easily facilitated and there will be no increase outside the budget for the business being carried out. Supported by the ability (skills) of good business actors, it is undeniable that business will bring the expected results. Elements of internal factors from business actors also dominate the implementation of business operations. Interest in entrepreneurship is motivated by individual motives in running their business. Motives within these individuals will facilitate the implementation of learning in entrepreneurial experience, bring up entrepreneurial personality, positive perceptions of entrepreneurial characteristics which ultimately lead to strong motivation in running a business.